SUSAGRI - sustainable development in agriculture - Luostarinen, Matti (gb, 1998)
The indicators for sustainable development in agriculture can be used for gauging the state of agriculture and rural areas and their future and for analysing biological, economic, social, regional, structural and political factors in a genuinely multidisciplinary manner. The relation of the environment, rural aeas and nature to the human individual and his activities in emphasised in analytics related to system dynamics and the identification of open models. Formalistic language and information and empirical results must be linked to the intuitive, qualitative or even introspective part of the information gathering systems. Indicators, monitoring, assessing, landscape, sustainable, policy, aims, limitations but also environmental management, sustainable development, economic policy, socio-economic sustainability and a new way of life, integration, network economy, new infrastructure (technology) and new social systems in rural areas are among the key words of this project.
Keywords: Ys; kestävä kehitys; indikaattori; strateginen suunnittelu; verkosto; rajoitukset; maisema; integraatio; verkostotalous; uusi infrastruktuuri; sustainable agriculture; indicators; strategic planning; network; integration; environmental management; monitoring; evaluation